The study of GMO between scholarly knowledge and knowledge to be taught An analysis of the didactic transposition process in a agro-ecological university course - Bocchi, Stefano; Nigris, Elisabetta; Passalacqua, Franco (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
The need of investigating academic didactics has been highlighted by many studies (Galliani, 2011; Felisatti, Serbati, 2014). This has been further emphasized by the recent introduction of the academic evaluation system, that ignites the debate on teaching methods (European Commission, 2013). The present research, conducted within the course of “Coltivazioni Erbacee” (degree in Management of cultivated plants and landscaping; Department of agricultural and environmental sciences, production, landscape, agroenergy at the University of Milan) during the academic year 2015/2016, has the purpose of testing and evaluating teaching methods’ in an academic context. Specifically the researchers have observed the outcomes in the first phases of didactic transposition (Chevallard, 1985), in regard to the acquisition of inter-disciplinary complex concepts that are characterized as “socially acute questions”. The researchers have conducted the didactic experimentation with a double approach (disciplinary and didactic) towards the transformation of “scholarly knowledge” in “knowledge to be taught” (Chevallard 1985; Develay, 1995; Astolfi, 2008). For this purpose, we have applied an immersive didactic methodology (Nigris, 2016; Rossi, 2012), built on the model of philosophical dispute (Nicolli, Cattani, 2006) and embodied simulation (Rossi, 2012; Caracciolo, 2014). The methodology chosen, referable to descriptive case study (Yin, 2006), has enhanced (according to Merriam 2002) both the use of different research methods (semi-structured interviews, focusgroups, semi-structured questionnaires) and interpretation perspectives during the analysis phases. Triangulation of data (Janesick, 2000) and investigators (Knafl, Breitmayer, 1993) enabled the identification and the dual reading – disciplinary and didactic – of some critical questions of the didactic transposition’s initial stage: the influence of the didactic dispositive (philosophical dispute and embodied simulation) in the construction of the learning objectives; the connection with the concept of “socially acute questions” (Legardez, Simonneaux, 2006).